Effects of Substituting the Two-Spotted Cricket (Gryllus bimaculatus) Meal for Fish Meal on Growth Performances and Digestibility of Striped Snakehead (Channa striata) Juveniles - Noratat Prachom; Bundit Yuangsoi; Jarongsak Pumnuan; Mohamed Ashour; Simon J. Davies; Ehab El-Haroun (My University, 2023)
This study aimed to investigate the potential of using field two-spotted cricket Gryllus bimaculatus as the main protein source in fish feed for striped snakehead (Channa striata) juveniles. A 10-week feeding effect on growth performance, feed utilization, digestibility of major nutrients, including amino acids, and physiological outputs of nitrogen and phosphorus were determined. A total of 225 C. striata juvenile fish (Initial weight, 15.0 ± 0.1 g) were randomly distributed into three dietary groups in triplicate (25 fish per rectangular aquarium within a semi-recirculating system). Each group was hand-fed one of the experimental diets containing the graded level of a cricket meal (CM) replacing 0%, 50%, and 100% (CM0%, CM50%, and CM100%, respectively) of fish meal (FM) protein component. The results showed that growth performance and protein retention tended to increase with increasing dietary CM levels, whereas the waste outputs of nitrogen (N) and phosphorus (P) decreased. Apparent net protein utilization (ANPU) and P retention values increased with increasing levels of cricket meal inclusion level in the diet. There was a significant reduction in both N and P solid waste and dissolved waste output for snakehead with increased CM inclusion. There were significant effects of CM level on fish whole-body composition in terms of elevated protein and fat content. In conclusion, the CM is a viable alternative protein source for aquaculture feeds and can be included up to 100% as a replacement for FM without compromising the growth performance of striped snakehead Channa striata juveniles. This may also have a more favorable impact, with the potential to reduce N and P loading to the environment.
Keywords: Snakehead; Gryllus bimaculatus; Insect Utilization and Effects